2018
DOI: 10.1080/19476337.2017.1420101
|View full text |Cite
|
Sign up to set email alerts
|

Stachyose combined with tea polyphenols mitigated metabolic disorders in high fructose diet-fed mice as studied by GC-MS metabolomics approach

Abstract: (2018) Stachyose combined with tea polyphenols mitigated metabolic disorders in high fructose diet-fed mice as studied by GC-MS metabolomics approach, CyTA -Journal of Food, 16:1,[516][517][518][519][520][521][522][523][524] To link to this article: https://doi.org/10. 1080/19476337.2017 High fructose (HF) ingestion is a common risk factor for the development of nonalcoholic fatty liver disease (NAFLD), which has become a serious health problem. The underlying mechanism of HFinduced NAFLD needs to be further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that high fructose mainly affects lipid peroxidation, butanoate metabolism, and fatty acid biosynthesis and metabolism. 17,18 Although the regulatory roles of amino acids as important substrates involved in metabolic pathways have been reported previously, [23][24][25] the amino acid components found by these studies were inconsistent. In the present study, high fructose led to dramatic alterations in l-serine, glycine, threonine, l-valine, l-aspartic acid, l-glutamic acid, pyroglutamic acid, tyrosine, and l-phenylalanine, suggesting that high fructose intake promoted changes in amino acids components.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Previous studies have shown that high fructose mainly affects lipid peroxidation, butanoate metabolism, and fatty acid biosynthesis and metabolism. 17,18 Although the regulatory roles of amino acids as important substrates involved in metabolic pathways have been reported previously, [23][24][25] the amino acid components found by these studies were inconsistent. In the present study, high fructose led to dramatic alterations in l-serine, glycine, threonine, l-valine, l-aspartic acid, l-glutamic acid, pyroglutamic acid, tyrosine, and l-phenylalanine, suggesting that high fructose intake promoted changes in amino acids components.…”
Section: Discussionmentioning
confidence: 89%
“…Under conditions of high fructose and increased maltose in starch and sucrose metabolism, d ‐glucose may facilitate the activation of glycine, serine, and threonine metabolism, before entering the TCA cycle via acetyl‐CoA. Previous studies have shown that high fructose mainly affects lipid peroxidation, butanoate metabolism, and fatty acid biosynthesis and metabolism 17,18 . Although the regulatory roles of amino acids as important substrates involved in metabolic pathways have been reported previously, 23–25 the amino acid components found by these studies were inconsistent.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Consumption of EA exacerbates hyperlipidemia and fatty liver change in zebrafish [6]. EA contributes to energy and lipid metabolism, and was confirmed as a potential biomarker for high fructose-induced nonalcoholic fatty liver disease (NAFLD) [7]. Studies have shown that EA causes apoptosis in a variety of cells [8][9][10], increased endoplasmic reticulum stress (ERS) and OS in diabetic mice [11], and activated NLRP3 inflammasome in macrophages [12], but its specific pathogenic mechanism in chronic diseases remains to be further studied.…”
Section: Introductionmentioning
confidence: 89%